Differential characteristics and driving forces of the spatial distribution of heritage trees in Luoyang, an ancient capital of China - Hou, Heping; Zhang, Longchong; Bi, Huitao; He, Jing; Cai, Enxiang; Ren, Wanqian (Frontiers in Environmental Science, 2022)
Heritage trees have important historical, landscape, and ecological value. Exploring the spatial distribution pattern of heritage trees is of great importance to the construction of ecological civilization and the connotation of regional history and culture. This paper took 5,216 heritage trees in Luoyang, an ancient capital of China, as the research object and used geospatial analysis methods and a geographically weighted regression model to analyze the differences and driving forces of the spatial distribution of heritage trees. Results show that (1) the heritage trees in Luoyang were primarily Gleditsia sinensis, Sophora japonica, and Platycladus orientalis, and more than half of these trees were under 300 years old; (2) the high-density area formed a distribution pattern of “three cores, one ring, and two belts,” and the distribution of heritage trees had a positive spatial autocorrelation; (3) different driving factors in different regions had complex influences on the spatial distribution of heritage trees, and the order of influence was as follows: area of forest and orchard land> elevation > number of POIs (points of interest) > distance to the nearest river > slope > number of immovable relics. The results could provide a comprehensive understanding of the spatial distribution of heritage trees to protect the ecological function of heritage trees and mine the cultural value of heritage trees.